Changes in the Quality of Life of Outpatients in Methadone Maintenance Treatment Clinics in Kathmandu Valley - Sapkota, Basanta; Tulachan, Pratikchya; Ojha, Saroj P; Chapagai, Manisha; Dhungana, Saraswati (Journal of Institute of Medicine Nepal, 2019)
Introduction Methadone maintenance treatment (MMT) is widely accepted treatment option for the opioid dependent individuals. The evaluation of the quality of life represents the assessment of the effectiveness of the treatment program. The study aimed to explore the impact of MMT program on clients’ quality of life in the first 6 months of treatment. Methods A total of 63 patients were recruited from the 5 different methadone clinics of Kathmandu valley. A prospective follow-up design was used. The semi-structured pro forma was filled up. To assess quality of life, WHO Quality of Life questionnaire (WHOQOL-BREF, 26-item version) was used. The tool was used to assess the quality of life at the baseline and after 6 months of enrollment in MMT program. Results Following 6 months of methadone maintenance treatment of opioid dependent individuals, significant improvements (P<0.001) were observed in all measured domains of quality of life i.e. physical, psychological, environmental and social. The least improvement was noted in the social domain. Conclusion Methadone maintenance treatment is helpful in improving the quality of the life of the opioid dependent individuals in MMT clinics.